Incorporação de agentes de ligação cruzada em sistemas adesivos aplicados em dentina afetada por cárie - Rolim, Deborah Cavalcante Magalhães (2020)
Caries-affected dentin (CAD) is a substrate widely found in clinical practice and in which there is a greater difficulty in adherence and higher rate of degradation. Natural crosslinking agents, such as proanthocyanidin (PA) and epigallocatechin-3-gallate (EGCG), have been researched for positive effects on mechanical properties and structuralstability of sound dentin (SD) overtime. In the first chapter, a systematic review of in vitro studies was conducted about the effect of crosslinking agents applied on carious dentin in the mechanical properties of this tissue and the maintenance of the resin-dentin interface integrity. The search strategies were used in 5 databases, obtaining 594 articles, of which 11 were included in the systematic review. All articles had a medium risk of bias. Controversies have been found in the literature regarding the long-term effect of the agents because there is no standardization in the studies regarding the mode/time of application nor the concentration employed. In the second chapter, an in vitro study, 96 selected healthy human third molars were divided into groups defined according to the following criteria: sound dentin or caries-affected dentin induced by microcosm biofilm model; Ambar Universal adhesive or Clearfil SE Bond adhesive; adhesive application with no incorporation of crosslinking agents or application with 1% PA or 1% EGCG (n = 8). After adhesive application, composite resin restoration was constructed incrementally and the teeth were sectioned for the microtensile test (μTBS). The sticks in each group were subdivided into two subgroups: 24-hours test and test after 12 months of storage in distilled water. The bond strength, fracture pattern and the number of premature fractures of the specimens were then observed. Three random sticks per group were selected for nanoinfiltration (NL) analysis. Two slices of the 24-hours CAD groups, as well as two slices of the sound control groups of the two adhesives used, were chosen for the in situ zymography test of the resin-dentin interface. Data were evaluated according to the statistical one-way ANOVA test and Bonferroni post-hoc test (p ˂ 0.05). No group showed a statistical difference in the comparison at different times (24 h x 12 M) regardless of the type of dentin. When applied to CAD, the incorporation of PA or EGCG showed no effect on bond strength, regardless of the evaluation time and the adhesive used (p> 0.05). The Ambar - PA group was the only group that showed a decrease in enzymatic activation and showed maintenance of the bond strength when the comparison between CAD x SD was made after 12 M (p = 0.451). The fracture pattern showed a high predominance of adhesive/mixed failures. All groups exhibit silver nitrate deposits along with the bonding interface. The effect of incorporating crosslinking agents depends on the adhesive used and the substrate type. The incorporation of PA in Ambar Universal adhesive maintained the bond strength values and also showed a decrease in enzymatic activity in CAD, which was not observed in EGCG.